Online Learning on Mathematics Learning Outcomes of Class II Students of SD Negeri 191320 Raya Tongah - Alexander Samosir; Fica Aulia Nanda; Chintani Sihombing (Asian Journal of Community Services, 2023)
Research to describe online learning information  results of learning mathematics for students learning to teach at home. Research using descriptive qualitative research. Sample of study were parents and teachers, class II students at SD Negeri 091320 Raya Tongah, totaling 25 people, namely 12 students, 12 parents and 1 class II teacher. Data collection techniques using documentation, interviews, observations namely. The results of the analysis of the research data obtained show that the impact experienced by students, teachers and parents learning activities of students' math scores has increased, what parents and teachers feel is still lacking in mastery of technology, additional internet quota fees, additional work in accompanying children learning, communication and socialization between students, teachers and parents is reduced.